Determinação da estrutura cristalina/molecular de um derivado da tiossemicarbazona com atividade farmacológica, a tetralona-tiossemicarbazona - Silva, Cecília Santos (2013)
The hydrochloric acid catalyzed reaction of 1-tetralone (10 mmol) and thiosemicarbazide (10 mmol) in a 3:1 mixture of ethanol and water (100 ml) was refluxed for 7 h. After cooling and filtering, crystals suitable for X-ray diffraction were obtained by recrystallization from tetrahydrofurane. The molecular structure of the tetralone-thiosemicarbazone, C11H13N3S, is not planar: the maximum deviation from the mean plane of the non-H atoms is 0.521 (2) A for an aliphatic C atom, which corresponds to an envelope conformation for the nonaromatic ring. The thiosemicarbazone moiety and the benzene ring have maximum deviations from the mean planes through the non-H atoms of 0.0288 (16) and 0.0124 (27) A, respectively, and the dihedral angle between the two planes is 8.84 (13)o. In the crystal, molecules are linked into chains by pairs of N-H¡E¡E¡ES hydrogen bonds along [1 -1 0], forming a one-dimensional H bonded polymer. The molecule shows an trans conformation for the atoms about the C1¡XN1/N1¡XN2/N2¡XC11 bonds. The cystal data are: space group monoclinic, C 2/c, a = 15.4388 (11) A, b = 5.5781 (3) A, c = 26.338 (2) A e Ò = 102.940 (6)o. Through 1H NMR spectrum was observed that the tautomeric thione form is predominant in solution. All starting materials were commercially available and were used without further purification. The synthesis was adapted from a procedure reported previously. This work is already published (Oliveira et al., Acta Cryst. (2012). E68, o2581).